2021
DOI: 10.21037/atm-20-6407
|View full text |Cite
|
Sign up to set email alerts
|

Role of a successful spontaneous breathing trial in ventilator liberation in brain-injured patients

Abstract: Background: Spontaneous breathing trials (SBTs) have been shown to improve outcomes in critically ill patients. However, in patients with brain injury, indications for intubation and mechanical ventilation are different from those of non-neurological patients, and the role of an SBT in patients with brain injury is less established. The aim of the present study was to compare key respiratory variables acquired during a successful SBT between patients with successful ventilator liberation versus failed ventilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
2
0
1
Order By: Relevance
“…However, while interest in the use of partially supported breathing modes is increasing [ 118 , 119 ], the role of spontaneous breathing [ 120 ] ventilation in patients with ABI is less well-established [ 121 ]. Spontaneous respiratory effort has been shown to be beneficial by improving gas exchange and oxygenation, haemodynamics, and non-pulmonary organ function [ 10 , 106 , 122 – 124 ].…”
Section: Ventilatory Strategies In Acute Brain Injury: What Is Different?mentioning
confidence: 99%
“…However, while interest in the use of partially supported breathing modes is increasing [ 118 , 119 ], the role of spontaneous breathing [ 120 ] ventilation in patients with ABI is less well-established [ 121 ]. Spontaneous respiratory effort has been shown to be beneficial by improving gas exchange and oxygenation, haemodynamics, and non-pulmonary organ function [ 10 , 106 , 122 – 124 ].…”
Section: Ventilatory Strategies In Acute Brain Injury: What Is Different?mentioning
confidence: 99%
“…1 ). We identified one additional study by citation searching, for 21 included studies (13, 14, 30–48). Additional study selection details are reported in eTables 1 and 2 (http://links.lww.com/CCM/H268).…”
Section: Resultsmentioning
confidence: 99%
“…En contraparte, Shi et al concluyen en su estudio que en pacientes con lesión cerebral la falla en la liberación del ventilador fue común después de una PVE exitosa (42). El análisis fisiológico en profundidad durante esta prueba no proporcionó datos para predecir la liberación exitosa en estos pacientes (42).…”
Section: ¿Qué Factores Se Asocian De Forma Independiente Al éXito De ...unclassified